Managed floating: Understanding the new international monetary order - Peter Bofinger; Timo Wollmershäuser (University of Würzburg, Department of Economics, 2001)
Although there seems to be a broad consensus among economists that purely floating or completely fixed exchange rates (the so-called corner solutions) are the only viable alternatives of exchange rate management, many countries do not behave according to this paradigm and adopt a strategy within the broad spectrum of exchange rate regimes that is limited by the two corner solutions. These intermediate regimes are characterized by significant foreign exchange market interventions of central banks and a certain degree of exchange rate flexibility. We develop a new empirical methodology that identifies three different forms of floating on the basis of a central bank's intervention activity: pure floating (no interventions), independent floating (exchange rate smoothing), and managed floating (exchange rate targeting). Our cross-country study shows that exchange rate targeting is at least as important as exchange rate smoothing. Subsequently we present a monetary policy framework in which central banks use the exchange rate as an operating target of monetary policy. We explain the mechanics of interventions and sterilization and we explain why a central bank has an interest of controlling simultaneously the exchange rate and the short-term interest rate. We derive the monetary policy rules for our two operating targets from a simple open economy macro model in which the uncovered interest parity condition and the Monetary Conditions Index play a central role.
Keywords: 330; exchange rate regime; monetary policy; interventions; sterilization; floating; Monetary Conditions Index